2021
DOI: 10.3389/fonc.2021.772165
|View full text |Cite
|
Sign up to set email alerts
|

Predictive Performance of Serum S100B Versus LDH in Melanoma Patients: A Systematic Review and Meta-Analysis

Abstract: BackgroundCurrently, no consensus on the use of blood tests for monitoring disease recurrence in patients with resected melanoma exists. The only meta-analysis conducted in 2008 found that elevated serum S100B levels were associated with significantly worse survival in melanoma patients. Serum LDH is an established prognostic factor in patients with advanced melanoma.ObjectiveTo compare the discriminative and prognostic ability of serum S100B with that of serum LDH in patients with melanoma.MethodsThis systema… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 73 publications
(96 reference statements)
0
12
0
Order By: Relevance
“…Among these proteins, two markers from the S100 family (EN-RAGE and S100A11) displayed particularly strong associations closer to diagnosis. Proteins in the S100 family are implicated in tumorigenesis and cancer progression through different mechanisms of inflammation, cell differentiation, and cell proliferation 31 , and have been proposed as biomarkers for prognosis of melanoma 32,33 . These observations suggest that the risk associations are likely to reflect a somatic response to (or the direct action of) a subclinical lung tumor, rather than differences in tobacco exposure.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among these proteins, two markers from the S100 family (EN-RAGE and S100A11) displayed particularly strong associations closer to diagnosis. Proteins in the S100 family are implicated in tumorigenesis and cancer progression through different mechanisms of inflammation, cell differentiation, and cell proliferation 31 , and have been proposed as biomarkers for prognosis of melanoma 32,33 . These observations suggest that the risk associations are likely to reflect a somatic response to (or the direct action of) a subclinical lung tumor, rather than differences in tobacco exposure.…”
Section: Discussionmentioning
confidence: 99%
“…32 These authors contributed equally: Karine Alcala, Florence Guida, Mikael Johansson, Karl Smith-Byrne, Victoria Stevens, Hana Zahed. 33 These authors jointly supervised this work: Mattias Johansson, Hilary A. Robbins.…”
Section: Reporting Summarymentioning
confidence: 99%
“…Therefore, the serum lactate dehydrogenase level in cancer patients increases, and lactate dehydrogenase is related to the prognosis of various malignant tumors [ 13 , 14 ]. Previous studies have shown that LDH is an independent risk factor for prognosis MM cases, and the serum LDH level in MM cases is high [ 15 , 16 ]. In addition, it has been reported that serum LDH levels have shown varying degrees of elevation, indicating anaerobic glycolysis in tissues before imaging manifestations in tumor cases.…”
Section: Discussionmentioning
confidence: 99%
“…Proteins in the S100 family have previously been proposed as biomarkers for prognosis of malignant melanoma. 48,49 We found limited evidence for heterogeneity in associations for most of the 36 markers when stratifying by smoking status, and little impact of additional adjustment for smoking characteristics. This suggests that the associations reflect a somatic response to (or the direct action of) a subclinical lung tumour, rather than differences in tobacco exposure.…”
Section: Epidemiological Properties Of Identified Proteinsmentioning
confidence: 75%
“…Proteins in the S100 family have previously been proposed as biomarkers for prognosis of malignant melanoma. 48,49…”
Section: Discussionmentioning
confidence: 99%